Epistemological Review of the Translation of Tajdid Words in Indonesian: A Contrastive Analysis Study - Fauzani, Naufal Syauqi; Wahyudin, Dedih; Nurfalah, Fikri; Rahman, Fathan Tibyan (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
The classification of Islamic movements—such as modernist, neo-modernist, traditionalist, reformist, revivalist, and fundamentalist—cannot be separated from the concept of tajdid as conveyed by the Prophet Muhammad (PBUH). However, the translation of tajdid into Indonesian using equivalent terms often results in semantic bias and detachment from the original epistemological framework of tajdid itself. This study aims to examine the epistemological perspective of translating the term tajdid into the Indonesian language. A qualitative approach was employed using descriptive-analytical methods based on library research. Data were collected through documentation techniques and analyzed using data inventory, classification, and interpretation. The findings reveal that direct translation of tajdid into Indonesian—using terms such as reformation, reformist, revivalist, or fundamentalist—frequently distorts the original epistemological structure embedded in tajdid. Therefore, this study recommends avoiding literal translations and instead suggests the use of transliteration as a more epistemologically appropriate and culturally sensitive alternative.